NIH Toolbox performance of persons with Parkinson's disease according to GBA1 and STN‐DBS status - Ahmad Almelegy; Srujanesh Gunda; Steven Buyske; Marc Rosenbaum; Sepehr Sani; Mitra Afshari; Leo V. Metman; Christopher G. Goetz; Deborah Hall; M. Maral Mouradian; Gian Pal (Annals of Clinical and Translational Neurology, 2024)
Abstract Objective Mutations in the glucocerebrosidase (GBA1) gene and subthalamic nucleus deep brain stimulation (STN‐DBS) are independently associated with cognitive dysfunction in persons with Parkinson's disease (PwP). We hypothesized that PwP with both GBA1 mutations and STN‐DBS are at greater risk of cognitive dysfunction than PwP with only GBA1 mutations or STN‐DBS, or neither. In this study, we determined the pattern of cognitive dysfunction in PwP based on GBA1 mutation status and STN‐DBS treatment. Methods PwP who are GBA1 mutation carriers with or without DBS (GBA1+DBS+, GBA1+DBS−), and noncarriers with or without DBS (GBA1−DBS+, GBA1−DBS−) were included. Using the NIH Toolbox, cross‐sectional differences in response inhibition, processing speed, and episodic memory were compared using analysis of variance with adjustment for relevant covariates. Results Data were available for 9 GBA1+DBS+, 14 GBA1+DBS−, 17 GBA1−DBS+, and 26 GBA1−DBS− PwP. In this cross‐sectional study, after adjusting for covariates, we found that performance on the Flanker test (measure of response inhibition) was lower in GBA1+DBS+ PwP compared with GBA1−DBS+ PwP (P = 0.030). Interpretation PwP who carry GBA1 mutations and have STN‐DBS have greater impaired response inhibition compared with PwP with STN‐DBS but without GBA1 mutations. Longitudinal data, including preoperative scores, are required to definitively determine whether GBA1 mutation carriers respond differently to STN‐DBS, particularly in the domain of response inhibition.